CRISPR/Cas9 Gene editing of RyR2 in human stem cell-derived cardiomyocytes provides a novel approach in investigating dysfunctional Ca2+ signaling. (July 2018) - Wei, Hua; Zhang, Xiao-Hua; Clift, Cassandra; Yamaguchi, Naohiro; Morad, Martin
Graphical abstract: Highlights: First creation of a CPVT1-associated RyR2 mutation by CRISPR/Cas9 in hiPSC-CM. Calcium signaling phenotype of gene edited cardiomyocytes is same as patient cells. The F2483I-RyR2 mutation is causative for CPVT1 arrhythmia. Creating CPVT1 pathology in healthy cells is an alternative way for rare mutations. Abstract: Type-2 ryanodine receptors (RyR2s) play a pivotal role in cardiac excitation-contraction coupling by releasing Ca 2+ from sarcoplasmic reticulum (SR) via a Ca 2+ -induced Ca 2+ release (CICR) mechanism. Two strategies have been used to study the structure-function characteristics of RyR2 and its disease associated mutations: (1) heterologous cell expression of the recombinant mutant RyR2s, and (2) knock-in mouse models harboring RyR2 point mutations. Here, we establish an alternative approach where Ca 2+ signaling aberrancy caused by the RyR2 mutation is studied in human cardiomyocytes with robust CICR mechanism. Specifically, we introduce point mutations in wild-type RYR2 of human induced pluripotent stem cells (hiPSCs) by CRISPR/Cas9 gene editing, and then differentiate them into cardiomyocytes. To verify the reliability of this approach, we introduced the same disease-associated RyR2 mutation, F2483I, which was studied by us in hiPSC-derived cardiomyocytes (hiPSC-CMs) from a patient biopsy. The gene-edited F2483I hiPSC-CMs exhibited longer and wandering Ca 2+ sparks, elevated diastolic Ca 2+ leaks, and smaller SR Ca 2+ stores, like those of patient-derived cells. Our CRISPR/Cas9 gene editing approach validated the feasibility of creating myocytes expressing the various RyR2 mutants, making comparative mechanistic analysis and pharmacotherapeutic approaches for RyR2 pathologies possible.